Jaminan Hak Nafkah Anak dalam Hukum Keluarga Islam - Daharis, Ade (LITERATUS, 2023)
This research was motivated by the negligence of a father regarding his obligation to provide support for his children after a divorce. The Marriage Law and the Compilation of Islamic Law state that child support is the obligation of a father. Divorce does not result in the loss of a father's obligation to provide support for his children. This research uses qualitative field research methods. The data sources used include primary sources in the form of interviews with divorced married couples. Secondary data sources include books, journals about divorce and post-divorce child support as well as statutory regulations. Data collection techniques were carried out by interviews. The analysis technique used is data management and data transcription.